ESL Teachers’ Approaches towards the Acceptance of Educational Technology Integration in Non-Formal Education: A Case from Kenya - Kildė, Laura (Journal of Education Culture and Society, 2023)
Aim. In efforts to handle the negative impact of the COVID-19 pandemic, language schools in Kenya were forced to organise a smooth transition from physical to virtual classroom by incorporating educational technologies in virtual learning and teaching processes. Such a shift was new to teachers and required additional efforts to master the peculiarities of organising virtual English classes. Thus, this study aims to explore Kenyan ESL teachers’ perspectives towards the acceptance of educational technology integration in non-formal education.Methods. A qualitative approach was adopted in this study. Eleven teachers from two private foreign language schools participated in semi-structured in-depth interviews, where they answered questions based on the elements of the Technology Acceptance Model (TAM).Results. The findings showed that most teachers’ approaches towards the acceptance of educational technologies were mainly positive and they intend to integrate them in their ESL classroom. The results of the qualitative data analysis also demonstrated that age is one of those personal characteristics that might hinder teachers’ willingness to adopt educational technologies while teaching ESL.Conclusions. This study also found that the variety of adopted educational technologies was not extensive. Therefore, teachers’ awareness, interest, and digital competences should be further developed.Practical application. The herein presented research findings are of a significant importance for the enhancement of teachers’ competences to apply educational technologies while teaching ESL in Kenya. It also has implications for the practice that is relevant for ESL teachers in non-formal education as well as curriculum organisers.Keywords: educational technologies, online learning technologies, Technology Acceptance Model (TAM), English as a Second Language (ESL), non-formal education